Using Pretest-Posttest Research Designs to Enhance Jury Decision-Making - Jane Goodman-Delahunty; Natalie Martschuk; Anne Cossins (Oñati Socio-Legal Series)
When lay jurors are unfamiliar with key evidentiary issues, expert evidence, judicial instructions and group deliberation may enhance their understanding of this evidence. Systematic steps to assess the relationship between juror biases in cases of child sexual abuse are offered as an example to illustrate a programmatic research approach. Using pretest-posttest research designs, the effectiveness of three traditional legal procedural safeguards to reduce common jury misconceptions in the context of simulated trials were tested and compared. By measuring mock-juror knowledge before and after each intervention, knowledge gains attributable to these interventions were distinguished from practice effects. Unexpected increases in acquittals following deliberation underscored the importance of adding adequate control groups and of testing deliberation effects in jury simulation studies. Benefits of this research paradigm to assist courts, legal counsel and policy makers in devising effective methods to enhance jury decisions in complex criminal cases are discussed.